Pembelajaran Materi Musik Tradisional Minangkabau Berbasis Kurikulum Mardeka di Kelas X SMA Negeri 1 Sungai Tarab - Satria Hanif; Robby Ferdian (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This study aims to analyze and evaluate the Minangkabau traditional music learning model/strategy applied in grade X of SMA Negeri 1 Sungai Tarab. The research to be used is qualitative research using analytical descriptive methods. This research instrument is the researcher himself and is assisted by supporting instruments such as stationery and cameras. Data collection techniques are carried out through observation, interviews, and documentation. The steps to analyze data are to collect data, describe the data and collect the data. The results showed that learning Minangkabau traditional music in Class X of SMA Negeri 1 Sungai Tarab was carried out with theory and practice. The implementation of theory in learning traditional music culture art was carried out for 2 weeks, starting from the first meeting, then for practical learning the teacher exemplified directly with several songs playing traditional Minangkabau musical instruments. Students are less interested in learning Minangkabau traditional music culture. Because teachers have not found the right learning model in learning, and also in practical learning face obstacles in the available musical instruments. Because it is not guarded / maintained to make some traditional Minangkabau musical instruments can no longer be used. Student interest in learning Minangkabau traditional music seems to be decreasing, because the learning model or strategy for teachers is not right, teachers have not implemented important stage assessments that must exist in learning that applies the curriculum and also the factors of inadequate tools used that make the learning process of Minangkabau traditional music art culture not run optimally.